2020
DOI: 10.3389/fncel.2020.00234
|View full text |Cite
|
Sign up to set email alerts
|

Berbamine Analogs Exhibit Differential Protective Effects From Aminoglycoside-Induced Hair Cell Death

Abstract: Hudson et al. Otoprotection of Berbamine Analogs exhibited protection when delivered after aminoglycoside removal. Based on our studies, berbamine analogs represent a promising tool to further understand the pathology of aminoglycoside-induced hearing loss and can serve as lead compounds to develop otoprotective drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…In zebrafish, it has been shown that treatment with quinoline ring derivatives such as amsacrine, quinine, and mefloquine protects against aminoglycoside-induced hair-cell death by blocking uptake (Ou et al, 2012). Analogs of the quinoline ring derivative berbamine have also recently been shown to block uptake of aminoglycosides into hair cells; however, the degree of uptake block did not correlate with the magnitude of hair-cell protection from aminoglycosides, suggesting a second uptake-independent mechanism (Kruger et al, 2016;Hudson et al, 2020). Quinoline ring derivatives have been shown to have antioxidant properties in other systems (Detsi et al, 2007;Naik et al, 2009;Ghinet et al, 2012).…”
Section: Mitochondrial Ros Production and Antioxidant Protection Agai...mentioning
confidence: 99%
“…In zebrafish, it has been shown that treatment with quinoline ring derivatives such as amsacrine, quinine, and mefloquine protects against aminoglycoside-induced hair-cell death by blocking uptake (Ou et al, 2012). Analogs of the quinoline ring derivative berbamine have also recently been shown to block uptake of aminoglycosides into hair cells; however, the degree of uptake block did not correlate with the magnitude of hair-cell protection from aminoglycosides, suggesting a second uptake-independent mechanism (Kruger et al, 2016;Hudson et al, 2020). Quinoline ring derivatives have been shown to have antioxidant properties in other systems (Detsi et al, 2007;Naik et al, 2009;Ghinet et al, 2012).…”
Section: Mitochondrial Ros Production and Antioxidant Protection Agai...mentioning
confidence: 99%
“…Male C57/BL6 mice (8 weeks old, 20-25 g body weight) were provided by the Laboratory Animal Center at the Air Force Medical University and housed in a controlled environment (22)(23)(24)(25)…”
Section: Animalsmentioning
confidence: 99%
“…BA derivatives can improve cell proliferation of ROS and target calcium/calmodulin‐dependent death protein kinase II. Therefore, BA may play a potential protective role in antitumor and cardiovascular protection 22–25 . Previous studies have shown that BA prevents cardiomyocyte death and injury by inhibiting mitochondrial oxidative stress and the inflammatory response 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Berbamine analogues protect against aminoglycoside-induced hair cell death in distinct ways. 40 Berbamine shields the heart from isoproterenol-induced myocardial infarction in rats via regulating the expression of eNOS and iNOS. 41 Through autophagy regulation, Berbamine post conditioning shields the myocardium from ischemia/reperfusion injury.…”
Section: Berbamine In Cancermentioning
confidence: 99%